1990
DOI: 10.1073/pnas.87.7.2555
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 induces early protein phosphorylation and requires only a short exposure for late induced secretion of beta-endorphin in a mouse pituitary cell line.

Abstract: Previous work has shown that prolonged pretreatment of a mouse anterior pituitary cell line, AtT-20 cells, with the cytokine interleukin 1 (IL-1) stimulates /3-endorphin release and potentiates the secretion induced by many secretagogues. Prolonged treatment with IL-1 abolishes the capacity of cytokine to induce the phosphorylation of 20-and 60-kDa proteins.The presence of IL-1 was required initially only for a short time to induce late secretion in AtT-20 cells. These observations indicate that once IL-1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…In concordance, several phosphorylation sites, present in the Nur77 protein, may be the target for p38 regulation. IL‐1 treatment of AtT‐20 cells stimulates the phosphorylation of a protein with the same molecular weight than Nur77 [32]. Further studies are required to identify whether p38 modulation is exerted by direct phosphorylation of Nur77 as is the direct phosphorylation of Nur77 by extracellular signal‐regulated kinase (ERK)2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…In concordance, several phosphorylation sites, present in the Nur77 protein, may be the target for p38 regulation. IL‐1 treatment of AtT‐20 cells stimulates the phosphorylation of a protein with the same molecular weight than Nur77 [32]. Further studies are required to identify whether p38 modulation is exerted by direct phosphorylation of Nur77 as is the direct phosphorylation of Nur77 by extracellular signal‐regulated kinase (ERK)2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, in some of these reports changes were marginal, and in other reports no direct effects of ILl on cAMP synthesis were observed in T-cells (Didier et al, 1988), osteosarcoma cells (Rodan et al, 1990), pituitary tumour cells (Fagarasan et al, 1990) or astrocytoma cells (Kasahara et al, 1990). Still further reports have shown that ILI could elevate intracellular cyclic AMP levels, but that this effect was poorly reproducible (Bomsztyk et al, 1990).…”
Section: Adp-ribosylation Studiesmentioning
confidence: 91%
“…Despite the finding that ILI stimulation induces production of diacylglycerol, evidence for a concomitant ILl-induced activation of protein kinase C is controversial (Abraham et al, 1987;Ostrowski et al, 1988;Munoz et al, 1990 lation has been reported to increase intracellular cAMP acutely in several cell types (Shirakawa et al, 1988;Zhang et al, 1988;Bomsztyk et al, 1990;Munoz et al, 1990) and to stimulate adenylate cyclase activity in membrane preparations (Shirakawa et al, 1988;Chedid et al, 1989). Others, however, have failed to observe cAMP responses to ILl (Didier et al, 1988;Shiroo & Matsushima, 1990;Fagarasan et al, 1990;Kasahara et al, 1990;Rodan et al, 1990), and in T-cells elevation of cAMP concentration by pharmacological agents was found to inhibit the ability of ILI to induce interleukin 2 (IL2) secretion (Rollins et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we have addressed the problem of the nature of the intracellular signals that are activated by the inflammatory mediators external to the liver cell. Recent 0309-1651/93/040425--08/$08.00/0 reports indicate that IL-l or TNF can induce in their target cells the phosphorylation of specific proteins (Bird and Saklatvala, 1989;Fagarasan et al, 1990): therefore we have analyzed the pattern of liver phosphoproteins during the early stages of acute-phase response induced in the rat by a subcutaneous injection of turpentine.…”
Section: Introductionmentioning
confidence: 99%